1986
DOI: 10.1042/bj2400559
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-dependent generation of a cytosolic dithiol which activates hepatic iodothyronine 5′-deiodinase. Demonstration by alkylation with iodoacetamide

Abstract: We have assessed a previously proposed mechanism mediating 5'-deiodinase activation involving enzymic reduction of disulphides to thiols in non-glutathione cytosolic components of Mr approx. 13,000 (Fraction B) catalysed by NADPH in the presence of other cytosolic components of Mr greater than 60,000 (Fraction A). The extent of Fraction B reduction under various experimental conditions was monitored by determining the amount of 14C incorporated into chromatographically isolated Fractions B and A after their al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Three components of CCS, DFA, DFB and NADPH, regulate the activation of 5'-DI by this CCS [7], and previous studies [7,8] are consistent with the proposal that the degree of activation by this system depends on the concentration of reduced DFB available for the reduction of the oxidized enzyme, ESI [19,20]. In the present study, the experimental conditions in which the concentration of reduced DFB depends on the amount of oxidized DFB were manipulated by varying the concentration of DFB at fixed concentrations of DFA and a constant excess of NADPH [8]. Since preliminary studies with nanomolar concentrations of rT3as substrate showed the optimal pH to be 7.5 and the optimal temperature to be 37°C for the reaction with both liver and kidney preparations, all experiments, whether performed with partially or highly purified CCS components, used these assay conditions.…”
Section: Purification Of Dfa and Dfbmentioning
confidence: 61%
See 1 more Smart Citation
“…Three components of CCS, DFA, DFB and NADPH, regulate the activation of 5'-DI by this CCS [7], and previous studies [7,8] are consistent with the proposal that the degree of activation by this system depends on the concentration of reduced DFB available for the reduction of the oxidized enzyme, ESI [19,20]. In the present study, the experimental conditions in which the concentration of reduced DFB depends on the amount of oxidized DFB were manipulated by varying the concentration of DFB at fixed concentrations of DFA and a constant excess of NADPH [8]. Since preliminary studies with nanomolar concentrations of rT3as substrate showed the optimal pH to be 7.5 and the optimal temperature to be 37°C for the reaction with both liver and kidney preparations, all experiments, whether performed with partially or highly purified CCS components, used these assay conditions.…”
Section: Purification Of Dfa and Dfbmentioning
confidence: 61%
“…Evidence has been presented suggesting that this system contains a cytosolic dithiol component of Mr approx. 13 000 (DFB) that is reduced by another cytosolic component of Mr > 60000 (DFA) (a putative reductase) in the presence of NADPH [7,8]. These studies utilized relatively crude cytosolic Fractions A and B containing DFA and DFB respectively and showed that this endogenous cofactor system, which supported the activity of a type I low-Km 5'-DI, had properties similar to those of the thioredoxin system [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro deiodinase assays usually use the nonphysiological reducing agent DTT, but Goswami and Rosenberg (21) purified from cells a protein thiol cofactor resembling glutaredoxin (Grx). Another group identified Trx and Trx reductase (TrxR) as cytosolic factors needed for Dio1 reduction (22)(23)(24), consistent with decreased Dio1 activity under conditions decreasing reduced Trx (25). Dio1 activity from liver measured with a physiological NADPH-dependent Trx/TrxR regenerating system was lower than with millimolar DTT but revealed a K m (Trx) of 1.8 μM and a K m [reverse T 3 (rT 3 )] of 1.4 nM, as well as sequential kinetics as in Dio2 and Dio3 (24).…”
mentioning
confidence: 99%
“…NOTE ADDED: After completion of the studies described above, our earlier suggestion that the thioredoxin system could account for the observed properties of the postulated DFA -DFB -NADPH 5'-deiodinase cofactor system, which operates at nanomolar but not micromolar concentrations of rT3 (Sawada et al 1986a;Das et al.…”
Section: Resultsmentioning
confidence: 94%
“…Although vitro 5'-deiodination of iodothyronines by isolated loss of cytosolic stimulating activity during starvation hepatic microsomes is markedly dependent upon added and its panial restoration GSH and NADPH thiols (Visser et al 1976; Goswami and Rosenberg and Ingbar 1979;Harris etal. 1979) suggest that GSH is the principal endogenous cofactor for deiodinase, other findings (Gavin et al 1980 (DFB) of Mr = 13 000 in fraction B and NADPH 'Author to whom all correspondence should be addressed at (Sawada et al 1986a(Sawada et al , 1986bDas et al 1986 For personal use only. (Holmgren 1985).…”
Section: Introductionmentioning
confidence: 97%